Component Sourcing Strategies of Multinationals: An Empirical Study of European and Japanese Multinationals - Swamidass, Paul M.; Kotabe, Masaaki (Journal of International Business Studies, 1993)
This is a study of component sourcing decisions of European and Japanese manufacturers for supplying their manufacturing operations in their home countries for export to the U.S. as well as their operations in the United States. Specifically, employing data from seventy-one multinational manufacturers of European and Japanese origin operating in the U.S., the study investigated the determinants of international sourcing decisions. The authors found support for the hypothesis that international sourcing could be explained using international plant location theory. The significance of this finding is that it offers a new theoretical framework to spur much needed research on the topic of international sourcing.